A Comparative Study on the Potentials of Mobile Commerce in Selective Countries in Asia and Europe - Manoharan, Sharmila (2010)
This research aims to empirically examine the factors that affect the mobile commerce or m-commerce services uptake in Malaysia. There were five factors examined in this study which are perceived usefulness, awareness, perceived ease of use, trust and pre conceived idea.